TREE OF LIFE: TEACHERS’ REFLECTION ON THEIR TEACHING CAREER - Khoi, Mai Ngoc (VNU Journal of Foreign Studies; Vol 34 No 5DO - 10.25073/2525-2445/vnufs.4305, 2018)
This article discusses the use of narrative inquiry in educational research and emphasizes the importance of giving teachers opportunities to self-reflect and share their insights with other colleagues. It presents the narratives collected after the first stage, data collection, of an on-going narrative project using the tool ‘Tree of life’ to facilitate teachers’ self-reflection on their teaching career as a professional development activity. This activity provides a large amount of teacher-generated data while allowing teachers to reflect on some critical incidents in their career and gain self-knowledge which is as crucial to good teaching as knowing students and the subject they teach. By telling their stories, teachers can come to know themselves better and really appreciate how much they have accomplished and grown during their career, thereby making appropriate and meaningful plan for future professional development.